Challenges faced by early childhood education learners from child-headed families in Cowdray Park schools: a case of Reigate primary schools in Bulawayo Metropolitan Province. - Mathuthu, Nontando (Midlands State University, 2020)
The study aimed at finding out the challenges faced by Early Childhood Education learners from child-headed families in Cowdray Park schools in Reigate District. It focused on the background of the study which revealed the statement of the problem and significance of the study. The study employed a number of qualitative research approach. The population of the study consisted of four school heads, sixty teachers and four thousand and sixty learners under Reigate District in Bulawayo Metropolitan Province. A sample consisted of twenty-four participants including teachers, school heads and learners. Questionnaires, interviews and observation were used to collect data from the study. Furthermore, the research targeted at presenting and analysing data using tables, pie chart and bar graphs. The study revealed that there are children who are from child-headed families and are not performing well academically in the selected schools. There were challenges that these children from child-headed families faced such as financial constraints, hunger to mention a few and these challenges led to poor performance in school. The study also revealed that children at the ages of six to thirteen are too young to source food and other basic needs for themselves. In addition, the study sought to discuss on the findings, summary and recommendations for teachers, school heads and Government. From the findings it was recommended that the school heads, teachers as well as the Government try to identify children who are living on their own without parental care so that they can assist them at the earliest time.